Politique énergétique et facteur 4 : instruments et outils de régulation à disposition des collectivités - Camille Chanard; Marie-Hélène de Sède-Marceau; Micael Robert (Développement Durable et Territoires)
Local authorities have, traditionally, many responsibilities in the energy field and, therefore, can influence on greenhouse gas emissions. They directly impact on energy chain with consumption in public buildings, supply networks and energy production equipments. They also impact on the triptych space-society-environment with land planning choices. The paper realises an overview of policy instruments and planning instruments that could be used by French local communities in order to structure energy and climate policy, taking into account whole public policies and actions realised on the area.